Two new species of philometrid nematodes (Philometridae), Barracudia notabilis n. sp. and Philometra consimilis n. sp., from the ovary of the hound needlefish Tylosurus crocodilus (Belonidae) off Florida, USA - Moravec F. (Sciendo, 2021)
Two new species of philometrid nematodes (Philometridae), Barracudia notabilis n. sp. and Philometra consimilis n. sp., are described from males found in the ovary of the hound needlefish Tylosurus crocodilus (Péron et Lesueur) (Belonidae) from off the Atlantic coast of Florida, USA. Both species are described and illustrated based on light and scanning electron microscopical examinations. Barracudia notabilis n. sp., the first representative of this genus from fishes in the Atlantic Ocean, can be differentiated from other congeners by the body length of the male (2.69 mm), the length of the gubernaculum (57 μm) and spicules (81 μm), and by the shape of the gubernaculum. Philometra consimilis n. sp. differs from all congeners mainly in the unique structure of the distal tip of the gubernaculum (bearing two smooth dorsal barbs) and the species is also characterized by the length of spicules (111 μm) and the length of the gubernaculum (84 μm). Further studies are needed to discover and describe so far unknown gravid females of Barracudia spp.